Microplastics in the Southern Ocean - Isobe, Atsuhiko; Uchiyama, Kaori; Uchida, Keiichi; 内田, 圭一; ウチダ, ケイイチ; Tokai, Tadashi (Marine Pollution Bulletin, 2017)
A field survey to collect microplastics with sizes < 5 mm was conducted in the Southern Ocean in 2016. We performed five net-tows and collected 44 pieces of plastic. Total particle counts of the entire water column, which is free of vertical mixing, were computed using the surface concentration (particle count per unit seawater volume) of microplastics, wind speed, and significant wave height during the observation period. Total particle counts at two stations near Antarctica were estimated to be in the order of 100,000 pieces km− 2 journal article